VISI KEPEMIMPINAN DIGITAL KEPALA SEKOLAH DASAR DI ERA TEKNOLOGI DIGITAL - Moh Muslim (Elementeris : Jurnal Ilmiah Pendidikan Dasar Islam, 2021)
The purpose of this study is to investigate the digital leadership of primary school principals in the era of digital technology. This research uses a qualitative approach using a case study research type. Data were collected by means of in-depth interviews, participant observation and documentation. Data analysis was performed using interactive analysis with the stages of data collection, data condensation, data presentation and conclusion drawing. To maintain data validity, triangulation techniques were used. Several research results concluded that the principal developed a vision which reflected an orientation towards developing a school vision based on the development of digital technology. Research findings 1) technology-based school management, 2) technology-based strategic planning, 3) technology-based group discussion forums, 4) technology-based periodic evaluation and 5) field experience-based program development.